Enteral tube feeding practices and associated factors among nurses working in South Wollo Zone Specialized and General Hospitals, Wollo, Ethiopia, 2022 - Ali Ahmed; Samuel Anteneh; Adem Hussien; Anwar Seid; Yaregal Semanew (Frontiers in Nutrition, 2024)
BackgroundEnteral tube feeding is recommended as a route for nutrient delivery in critically ill patients. The practice of enteral tube feeding by nurses significantly influences patient treatment outcomes. Therefore, this study aimed to identify the practices of enteral tube feeding and the associated factors among nurses working in South Wollo Zone Specialized and General Hospitals, Wollo, Ethiopia, 2022.MethodsA hospital-based cross-sectional study design was conducted on 420 nurses from 1st August to 1st September 2022. Simple random sampling methods were used to select study participants. Data were collected using self-administered questionnaires and an observational checklist. The data were entered into Epi Data version 4.6 and analyzed using SPSS version 26. Variables with a p-value <0.05, a 95% confidence interval, and an adjusted odd ratio were considered to be significantly associated with enteral tube feeding practice.ResultA total of 400 nurses participated in the study, yielding a 95.2% response rate. The overall good practice of enteral tube feeding among nurses was 114 (28.5%) with a 95% CI of 23.8–33. Enteral tube feeding practice was significantly associated with a lack of adequate resources (AOR = 0.359, 95% CI: 0.192–0.673), unfamiliarity with current guidelines (AOR = 0.346, 95% CI: 0.203–0.586), lack of awareness (AOR = 0.511, 95% CI: 0.306–0.673) and the thermal effect of food (AOR = 0.56, 95% CI: 0.348–0.889).ConclusionThe enteral tube feeding practice among nurses was found to be 28.5%. Significant determinants of enteral tube feeding practice included a lack of awareness, inadequate resources in the institution, and unfamiliarity with the current guidelines for enteral feeding. To improve enteral feeding practices, it is recommended that sufficient resources be provided, guidelines be made readily available, and training programs be conducted for the nursing staff.